Acute Leukoencephalopathy with Diffusion Restriction in a Toddler - Siva Vyasam; Jyothi Jayaram; Naga Anudeep Mylavarapu; Anuj Guleria; Siddharth Khanna; Renu Suthar; Suresh Kumar Angurana (Current Medical Issues)
We report a case of acute leukoencephalopathy with restricted diffusion (ALERD) in a 2½-year-old male who presented with fever, seizures, and altered sensorium. Cerebrospinal fluid showed lymphocytic pleocytosis, whereas brain magnetic resonance imaging revealed T2 hyperintensities with restricted diffusion in cortical and subcortical regions. The patient was treated with antiseizure medications, acyclovir, methylprednisolone, and intravenous immunoglobulin. This case highlights the importance of early recognition and prompt treatment of ALERD in children, emphasizing the need for increased awareness among pediatric healthcare providers to improve patient outcomes.